Kesan perbezaan jantina dan aliran ke atas ujian putaran mental (Mental rotation test, MRT) di kalangan pelajar sekolah menengah - Khairul Najua, Abdul Hanif. (Universiti Malaysia Sarawak, UNIMAS, 2006)
This research was conducted to Form Five Student from three different stream schools ; Sekolah Menengah Sains Matang, Sekolah Menengah Kebangsaan Tun Abang Haji Openg, dan Sekolah Menengah Teknik Matang, where 78 respondents were involved. Objectively, this research was to determine the effect of gender and stream of education on Mental Rotation Test among secondary school students. The specific objective was to compare the result of the lowest male student in all of three streams to the highest performance female students in all three streams. The instrument for this research was an experimental design which uses Coglab on CD (Mental Rotation Test). Inferential statistics method that is two ways independent ANOVA was used to analyze research’s hypotheses. This method showed that there was a significant difference between genders on MRT. This situation explained that male student showed better performance than female students. The ANOVA also indicated the differences between streams on MRT. From the Post Hoc test, it showed that there is significant different between student from Art stream and student from Science stream. Besides that, there was also significant different between student from Art stream and student from Technical stream. However, there is no significant different between Science stream’s student and Technical stream’s student. Moreover, the result from ANOVA indicated that there was no significant between gender and stream on Mental Rotation Test among respondent. However, the result from data analysis showed that female Science stream student and female Technical stream student outperformed male from the Art stream. As the conclusion, the education background plays an important roleto improve one’s spatial ability.